Site-Specific Reactivity of Nonenzymatic Lysine Acetylation - Baeza, Josue (ACS Chem Biol, 2015)
[Image: see text] Protein acetylation of lysine ε-amino groups is abundant in cells, particularly within mitochondria. The contribution of enzyme-catalyzed and nonenzymatic acetylation in mitochondria remains unresolved. Here, we utilize a newly developed approach to measure site-specific, nonenzymatic acetylation rates for 90 sites in eight native purified proteins. Lysine reactivity (as second-order rate constants) with acetyl-phosphate and acetyl-CoA ranged over 3 orders of magnitude, and higher chemical reactivity tracked with likelihood of dynamic modification in vivo, providing evidence that enzyme-catalyzed acylation might not be necessary to explain the prevalence of acetylation in mitochondria. Structural analysis revealed that many highly reactive sites exist within clusters of basic residues, whereas lysines that show low reactivity are engaged in strong attractive electrostatic interactions with acidic residues. Lysine clusters are predicted to be high-affinity substrates of mitochondrial deacetylase SIRT3 both in vitro and in vivo. Our analysis describing rate determination of lysine acetylation is directly applicable to investigate targeted and proteome-wide acetylation, whether or not the reaction is enzyme catalyzed.